2020
DOI: 10.20944/preprints202004.0180.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothesis: mPGES-1-Derived Prostaglandin E2, a So Far Missing Link in COVID-19 Pathophysiology?

Abstract: With frequencies varying up to 20%, treatment resistant pulmonary failure is a major life-threatening complication in COVID-19 (SARS-CoV-2, HCoV19) disease pathology. Both acute respiratory distress syndrome (ARDS), proposed to be caused by an over-reacting immune system which floods the lung with edema, a liquid consisting of inflammatory cells, and diminished lung perfusion, have been postulated to cause this treatment resistant lung failure. Aging, co-morbidities, male gender and obesity are pre-existing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…Indeed, elevated levels of PGE 2 were observed in patients infected with SARS-CoV-1 or SARS-CoV-2 (Hong et al, 2020;Lee et al, 2004). Furthermore, Smeitink et al (2020) (Figure 3).…”
Section: Potential Roles Of Pge 2 In Covid-19mentioning
confidence: 92%
“…Indeed, elevated levels of PGE 2 were observed in patients infected with SARS-CoV-1 or SARS-CoV-2 (Hong et al, 2020;Lee et al, 2004). Furthermore, Smeitink et al (2020) (Figure 3).…”
Section: Potential Roles Of Pge 2 In Covid-19mentioning
confidence: 92%
“…Following viral infection, an activation of immune response occurs, which includes the release of inflammatory mediators, such as pro-inflammatory cytokines (IL-6, IL-1 β, TNF-α) and eicosanoids (prostaglandins and leukotrienes) [3]. The second isoform of cyclooxygenase (COX-2) is responsible for producing the major part of PGs that are responsible for pain and inflammation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, the SARS coronavirus responsible for the 2003 outbreak increased the production of PGs by binding to COX-2 [4]. Different studies have demonstrated that PGE 2 increases the viral pathogenicity in many viral infections such as CMV, RB, RSV, HSV, EV71, and CVB2 by interfering with the viral transcription translation and/or replication [3]. However, we should also consider that in some cases, such as in HBV and PIV3, PGE 2 can either stimulate or inhibit the viral pathogenicity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, inculcation of omega-3 and omega-6 PUFAs in diet could serve as a major therapeutic tool for this novel virus, COVID-19. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) possess anti-inflammatory properties, resulting in the lower level of these inflammatory eicosanoids produced from arachidonic acid that inhibits NFκβ (nuclear factor kappa-light-chain-enhancer of activated B cells) signalling, leading to lesser production of inflammatory cytokines [47][48][49]. In a study, animal models with lung injury showed that administration of fish oil lessens pulmonary accumulation of neutrophils with reduced lung permeability, pulmonary oedema, and cardiopulmonary dysfunction [50].…”
Section: Role Of Nutritionmentioning
confidence: 99%